Rapid changes in biomass burning aerosols by atmospheric oxidation. Issue 7 (11th April 2014) - Vakkari, Ville; Kerminen, Veli‐Matti; Beukes, Johan Paul; Tiitta, Petri; van Zyl, Pieter G.; Josipovic, Miroslav; Venter, Andrew D.; Jaars, Kerneels; Worsnop, Douglas R.; Kulmala, Markku; Laakso, Lauri
Abstract: Primary and secondary aerosol particles originating from biomass burning contribute significantly to the atmospheric aerosol budget and thereby to both direct and indirect radiative forcing. Based on detailed measurements of a large number of biomass burning plumes of variable age in southern Africa, we show that the size distribution, chemical composition, single‐scattering albedo, and hygroscopicity of biomass burning particles change considerably during the first 2–4 h of their atmospheric transport. These changes, driven by atmospheric oxidation and subsequent secondary aerosol formation, may reach a factor of 6 for the aerosol scattering coefficient and a factor >10 for the cloud condensation nuclei concentration. Since the observed changes take place over the spatial and temporal scales that are neither covered by emission inventories nor captured by large‐scale model simulations, the findings reported here point out a significant gap in our understanding on the climatic effects of biomass burning aerosols. Key Points: A large number of biomass burning plumes were observed in southern Africa Cloud activating and optical properties change rapidly during plume transport The changes in climatically relevant properties depend on atmospheric oxidation